2022
DOI: 10.1001/jamanetworkopen.2022.28244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biannual Mass Azithromycin Distributions to Preschool-Aged Children on Trachoma Prevalence in Niger

Abstract: IMPORTANCEBecause transmission of ocular strains of Chlamydia trachomatis is greatest among preschool-aged children, limiting azithromycin distributions to this age group may conserve resources and result in less antimicrobial resistance, which is a potential advantage in areas with hypoendemic trachoma and limited resources. OBJECTIVE To determine the efficacy of mass azithromycin distributions to preschool-aged children as a strategy for trachoma elimination in areas with hypoendemic disease. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…District-level PCR from Alefa and Woreta town were estimated to be 0%, and a recent study from the same population in Dosso found no Ct in pooled metagenomic testing of ocular swabs. 36 In these three populations, 98% of clusters (60/61) fell below the serologic thresholds for 90% sensitivity, supporting the interpretation of low levels of infection below the estimated thresholds.…”
Section: Resultsmentioning
confidence: 51%
“…District-level PCR from Alefa and Woreta town were estimated to be 0%, and a recent study from the same population in Dosso found no Ct in pooled metagenomic testing of ocular swabs. 36 In these three populations, 98% of clusters (60/61) fell below the serologic thresholds for 90% sensitivity, supporting the interpretation of low levels of infection below the estimated thresholds.…”
Section: Resultsmentioning
confidence: 51%
“…1 and 2 ). District-level PCR from Alefa and Woreta town, Ethiopia were estimated to be 0%, and a recent study from the same population in Dosso, Niger found no C. trachomatis in pooled metagenomic testing of ocular swabs 38 . In these three populations, 98% of clusters (60/61) fell below the serologic thresholds for 90% sensitivity, supporting the interpretation of low levels of infection below the estimated thresholds.…”
Section: Resultsmentioning
confidence: 98%
“…We combined serologic, molecular, and clinical measurements collected between 2012 and 2019 across nine studies in five countries (Supplementary Table 1 ) 26 38 . When possible, measurements within the same study were stratified into populations corresponding to trachoma evaluation units, resulting in 14 study populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful follow-up studies of nasopharyngeal specimens among recipients of MAA in Niger show an increase in macrolide resistance among Streptococcus pneumoniae nasopharyngeal isolates, although this was not shown to persist by 36 months. 5 Given that no impact of MAA has been shown on ocular trachoma in Niger, 6 the original reason for mass azithromycin use, questions have to be asked as to the viability of this approach in the country, especially compared with other investments. No country has rolled out this strategy, more than 3 years following the conditional recommendation by the World Health Organization, 7 and findings from replication trials are still awaited.…”
mentioning
confidence: 99%